Mouse Striatal Dopamine Nerve Terminals Express α4α5β2 and Two Stoichiometric Forms of α4β2*-Nicotinic Acetylcholine Receptors - Grady, Sharon R. (J Mol Neurosci, 2009)
Wild-type and α5 null mutant mice were used to identify nicotinic cholinergic receptors (nAChRs) that mediate α-conotoxin MII (α-CtxMII)-resistant dopamine (DA) release from striatal synaptosomes. Concentration–effect curves for ACh-stimulated release (20 s) were monophasic when wild-type synaptosomes were assayed but biphasic with synaptosomes from the α5 null mutant. Deleting the α5 gene also resulted in decreased maximal ACh-stimulated α-CtxMII-resistant DA release. When a shorter perfusion time (5 s) was used, biphasic curves were detected in both wild-type and α5 null mutants, indicative of high- and low-sensitivity (HS and LS) activity. In addition, DHβE-sensitive (HS) and DHβE-resistant (LS) components were found in both genotypes. These results indicate that α-CtxMII-resistant DA release is mediated by α4α5β2, (α4)(2)(β2)(3) (HS), and (α4)(3)(β2)(2) (LS) nAChRs.